2004
DOI: 10.1038/nn1210
|View full text |Cite
|
Sign up to set email alerts
|

The X-linked mental retardation protein oligophrenin-1 is required for dendritic spine morphogenesis

Abstract: Of 11 genes involved in nonspecific X-linked mental retardation (MRX), three encode regulators or effectors of the Rho GTPases, suggesting an important role for Rho signaling in cognitive function. It remains unknown, however, how mutations in Rho-linked genes lead to MRX. Here we report that oligophrenin-1, a Rho-GTPase activating protein that is absent in a family affected with MRX, is required for dendritic spine morphogenesis. Using RNA interference and antisense RNA approaches, we show that knock-down of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
292
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(306 citation statements)
references
References 49 publications
11
292
1
2
Order By: Relevance
“…In young cultured neurons, oligophrenin1 colocalizes with the actin cytoskeleton in the growing tip of dendrites 257 , and is detected in the axon, dendrites and dendritic spines of mature neurons 258 . In vitro, the use of RNA interference methods has revealed the important role of oligophrenin1 in the regulation of dendrite morphogenesis and the regulation of dendritic spine maturation 258 . Notably, the downregulation of oligophrenin1 expression in rat hippocampal slices leads to a decrease in spine length without affecting spine density 258 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In young cultured neurons, oligophrenin1 colocalizes with the actin cytoskeleton in the growing tip of dendrites 257 , and is detected in the axon, dendrites and dendritic spines of mature neurons 258 . In vitro, the use of RNA interference methods has revealed the important role of oligophrenin1 in the regulation of dendrite morphogenesis and the regulation of dendritic spine maturation 258 . Notably, the downregulation of oligophrenin1 expression in rat hippocampal slices leads to a decrease in spine length without affecting spine density 258 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…OPHN1 is expressed in multiple tissues with the highest expression in the developing brain, where it is found in neurons of all major regions, including hippocampus, cerebellum and cortex, and is present in axons, dendrites and spines [24,30]. The OPHN1 protein negatively regulates RhoA, Rac1, and Cdc42 in vitro, in non-neuronal and neuronal cells [8,24].…”
Section: Oligophrenin-1mentioning
confidence: 99%
“…The OPHN1 protein negatively regulates RhoA, Rac1, and Cdc42 in vitro, in non-neuronal and neuronal cells [8,24]. Significantly, recent studies by Govek et al showed that knock-down of OPHN1 expression in CA1 pyramidal neurons in hippocampal slices results in a significant decrease in dendritic spine length [30]. As spine morphology is ultimately linked to synaptic function [89], such spine morphological changes are likely to compromise synaptic plasticity, and potentially lead to learning and memory deficits.…”
Section: Oligophrenin-1mentioning
confidence: 99%
See 2 more Smart Citations